Sudan : Second Review Under the Staff-Monitored Program and Request for Extension-Staff Report; and Statement by the Executive Director for Sudan. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
The transitional government embarked on a Staff-Monitored Program (SMP) in 2020 to help address major macroeconomic imbalances caused by decades of mismanagement, lay the groundwork for inclusive growth, and establish a track record of sound policies required for eventual HIPC debt relief. The economic challenges facing the authorities remain significant and have been exacerbated by the COVID-19 pandemic, but there have been improvements in both the domestic and external environment. Sudan has cleared its arrears to the World Bank and African Development Bank thereby regaining access to multilateral grant funding. A financing package for the clearance of arrears to the IMF has been identified, and on May 17, 2021 a development partner conference was held in Paris with a side event to promote investment in Sudan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Sudan